HUBUNGAN PENGETAHUAN TENTANG PENCEGAHAN GASTRITIS DENGAN POLA MAKAN PADA REMAJA - Kennygya Ahadysta Austin Devanka; Astri Handayani (Jurnal Akta Trimedika, 2024)
Adolescents is the ages that most often suffer from gastritis, it has an impact on their old age because it can interfere with the digestive system. Risk factors for gastritis can be caused by many things, one of which is due to a poor diet. It is said that adolescents are the most contributors who experience gastritis so it is necessary to provide early knowledge about gastritis prevention to avoid gastritis in old age. The purpose of the study was to assess the relationship between knowledge about gastritis prevention and diet. This study used a cross sectional approach. The number of respondents in this study was 241 respondents. The location of this study was at SMAN 50 East Jakarta. Data will be analyzed using the Chi Square test with a degree of significance of 95% and carried out within the confidence limit (α = 0.05). There is a relationship between gastritis prevention knowledge and diet (p=0.001).